The Postmodernism in Serbian Literature Within the Anglophone Theories: After the Eighties - Gordić Petković, Vladislava S. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The fiction written by Serbian authors in the eighties and beyond persistently constructs an entirely new world, in which existentialism and metaphysics, myth and literature, literary authors and their projection into literary characters intertwine regularly and legitimately. The narrative strategies borrowed from magic realism and American postmodernism delineate a hybrid world where citations and dreams, science and conspiracy, facts and the reinvention of facts converge and intersect.A case in point is Đorđe Pisarev, who works with the influences of Gothic fiction, Edgar Allan Poe’s detective stories and Stephen King’s horror alike. The continuous existential and psychological disintegration to which the author subjects his characters conditions the emergence of a multilayered narrative world. Within this world, the author not only disempowers the narrator but also transforms his skillfully crafted persona into a character open to deconstruction and characterized by existential and epistemological inconsistency.
Keywords: postmodernism; experiment; literary character; quotation